(untitled) (International Journal of Biomedical Research, 2014)
Objectives : To compare the onset, duration , postoperative pain scores ,time of first rescue analgesic required in supraclavicular block with local anaesthetic solution along with midazolam 50 g /kg . Methods : A randomized double blind study was carried out on 70 patients of ASA grade I and II undergoing upper limb orthopaedic surgeries ,were divided in two groups. Group A(n=35 ) received Inj. Bupivacaine (0.5%) 20 ml + Inj. Lignocaine with adrenaline (1:200000) 10ml .Group B(n=35) received Inj. Bupivacaine 0.5% (20 ml) + Inj. Lignocaine with adrenaline (1:200000) 10 ml + Inj. Midazolam 50 g/kg as an adjuvant in supraclavicular brachial plexus block .The duration of sensory block, motor block, duration of post operative analgesia, sedation score and visual analogue score were obtained in both groups and values were compared with ’unpaired t-test. Result : The onset and duration of sensory and motor block was significantly faster and longer in group B compared to group A (p 0.05). Pain scores were significantly lower in group B for 24 hours postoperatively (p 0.001). Demand for rescue analgesic were significantly less in group B. (p 0.05). Conclusion : the addition of midazolam to local anaesthetics in supraclavicular block prolongs onset and duration of blockade ,enhances post op analgesia with stable hemodynamic and desirable sedation score without any adverse effects.